2021
DOI: 10.1186/s12880-021-00642-z
|View full text |Cite
|
Sign up to set email alerts
|

Hahn-PCNN-CNN: an end-to-end multi-modal brain medical image fusion framework useful for clinical diagnosis

Abstract: Background In medical diagnosis of brain, the role of multi-modal medical image fusion is becoming more prominent. Among them, there is no lack of filtering layered fusion and newly emerging deep learning algorithms. The former has a fast fusion speed but the fusion image texture is blurred; the latter has a better fusion effect but requires higher machine computing capabilities. Therefore, how to find a balanced algorithm in terms of image quality, speed and computing power is still the focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…rough the dynamic guidance of intraoperative realtime fusion imaging technology, fusion imaging can locate the tumor more accurately and display the adjacent tumor in real time, which shortens the time for the operator to think about the location, scope, and adjacent structure of the tumor during the operation [34]. It reduces unnecessary brain tissue damage caused by exploration and search for tumors to speed up the postoperative recovery of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…rough the dynamic guidance of intraoperative realtime fusion imaging technology, fusion imaging can locate the tumor more accurately and display the adjacent tumor in real time, which shortens the time for the operator to think about the location, scope, and adjacent structure of the tumor during the operation [34]. It reduces unnecessary brain tissue damage caused by exploration and search for tumors to speed up the postoperative recovery of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [10] proposed a Gabor representation method that combines multiple CNNs and fuzzy neural networks to address the issue of inadequate representation of complex textures and edge information of lesions in fused multimodal medical images.Li et al [11] presented a multimodal medical image fusion approach that combines CNN and supervised learning. This method can handle various types of multimodal medical image fusion problems through batch processing, enhancing the overall efficiency and applicability of the technique.Guo et al [12] proposed an end-to-end CNN fusion framework based on a Pulse Coupled Neural Network (PCNN). In the feature fusion module, feature maps combined with a pulse coupled neural network were utilized to minimize information loss caused by convolution in the preceding fusion module, consequently improving computational efficiency.…”
Section: Medical Image Fusion Based On Convolutionalmentioning
confidence: 99%
“…Due to the vast success in a variety of applications, CNN has been adopted in several medical applications where imagery inputs are analyzed for diagnosis or classification. In the field of medical imaging, CNN has been successfully utilized for histological microscopic image [47], pediatric pneumonia [48], diabetic macular edema [48], ventricular arrhythmias [49], thyroid anomalies, mitotic nuclei estimation [50,51], neuroanatomy [52], and others [10][11][12][13][53][54][55][56][57][58][59]. Kermany et al [48] showed that CNN can detect diabetic macular edema and age-related macular degeneration with high accuracy and with a comparable performance of human experts.…”
Section: Cnn With Medical Imagesmentioning
confidence: 99%